Impact of national health city campaign on public health in China - Wenjing Wang; Songjiang Liu; Bingnan Guo (Frontiers in Public Health)
IntroductionEstablishing a national health city is an important national policy aimed at optimizing urban environment and improving residents’ health. A rigorous evaluation of the policy’s impact on China’s public health is imperative. Such an evaluation would provide a scientific foundation for the continuous improvement of the policy and enhance the overall health of the population.MethodsBased on the panel data of 84 prefecture-level cities in China from 2011 to 2023, this study takes healthy cities as a quasi-natural experiment, and employs a DID model to deeply explore the impact of the National Health City Campaign (NHCC) on public health in China.ResultsThe research indicates that the policy has led to a decline in mortality rates and has contributed to the enhancement of public health in China to a certain extent. The impact of the NHCC varies across different regions, economic development levels, and population sizes. In addition, this study determined that the NHCC is capable of achieving substantial enhancements in public health levels by promoting the optimization and upgrading of industrial structure. The impact of the sewage treatment rate on public health levels is found to be regulatory in nature.DiscussionThis study is instrumental in enhancing public health policy, providing a theoretical foundation for the development of a healthy city, and plays a pivotal role in the promotion of the Healthy China Initiative.